Case report: Echocardiographic diagnosis of double orifice mitral valve in an asymptomatic woman - Deng, Zixian; Wang, Xiaoyu; Liu, Qiyun; Li, Jianghua; Liu, Huadong (Frontiers in Cardiovascular Medicine, 2023)
Double orifice mitral valve is a rare congenital anomaly that is often associated with cardiac malformation. Patients usually present with valve dysfunction in childhood so that is diagnosed, while its prevalence and prognostic relevance in adulthood are unknown. We here report a 38-year-old female， who presented to the outpatient clinic due to an abnormal electrocardiogram， with isolated double orifice mitral valve malformation found by transthoracic echocardiography. Echocardiography is the preferred diagnosis for patients with double orifice mitral valve. It should be familiar with characteristics of echocardiogram, thereby improving the diagnostic rate and reducing missed diagnoses.